Farmyard Manure as K-Fertilizer Modulates Soil Biological Activities and Yield of Wheat Using the Integrated Fertilization Approach - Kumar, Sanjeev; Dhar, Shiva; Barthakur, Sharmistha; Rajawat, Mahendra Vikram Singh; Kochewad, S. A.; Kumar, Sudhir; Kumar, Dileep; Meena, L. R. (Frontiers in Environmental Science, 2021)
Potassium fertilization is often ignored by assuming alluvial soils have sufficient K reserves in the north-western plain zones of India under cereal-based cropping systems. There is scanty information on the impact of integrated K fertilization on soil enzymes, nutrients availability, microbial population and wheat yield cultivated in the corn wheat cropping system. The current study exhibited that treatment (T7) applied with a dose of 90 kg K ha-1 (30 kg K by FYM and 60 kg K by MOP) significantly enhanced the various microbial populations ranged from 48.00% to 123.10% and 39.00% to 124.00%, soil enzymatic activities ranged from 70.31% to 180.00% and 102.42% to 175.68%, available nutrients ranged from 2.43% to 8.44% and 14.79% to 22.87% for the first and second year of wheat cultivation. It also improved the various yield parameters (12.39% to 41.71% and 18.24% to 41.14%) during both consecutive years of cultivation. Statistical analysis revealed that the treatments (T4, T5, and T7) applied with integrated fertilization of wheat through FYM and MOP was more promising for improving soil enzymatic activities (11.59% to 57.22%), microbial populations (5.14% to 15.70%), available nutrients in soil (7.60% to 16.54%), and crop yield (1.06% to 5.85%) during the second year of cultivation as compared to the first year of cultivation. This study might be helpful to reclaim soil health and reduce chemical fertilizers used in agricultural lands.